Horizontal and Vertical Divisibility of Language Continuum: variants of the 21st century discourse from the perspective of an ordinary member of language community - Aliūkaitė, Daiva (Taikomoji kalbotyra, 2013)
The paper deals with the representative systems of the Lithuanian language from the perspective of ordinary members of language community. The empirical data includes the names and nominations of the language variants given by ordinary members of language community. The data for the research was collected during the preliminary stage of the implementation of the research project Lithuanian Language: ideals, ideologies and identity shifts focusing on the analysis of prestigious aspects of the varieties of the Lithuanian language, language ideals, language ideologies, etc. The paper is an attempt at the typologization of discourse variants identified by ordinary members of language community by estimating the (lack of) correspondence of the variants with geolinguistic and sociolinguistic language variants offered by scholars within certain scientific paradigms. Geolinguistic and sociolinguistic perspectives identify discursive variants according to objective differences and degree of their distinction. The investigation has manifested that the taxonomy of discursive variants suggested by ordinary members of language community helps locate oneself in the holistic space of the national language. The arguments raised in support of the above taxonomy include language facts as well as intuition, or the claim of I think that this is so type. Thus the isoglosses of perception of ordinary members of language community divide the national language continuum into a large number of segments. The respondents tend to give the status of ’variety’ to the large, objectively independent representational systems, cf., Highland dialect, Lowland dialect, etc.; and to the representational systems that do not have the value of ’variety’ from the perspective of a researcher, cf., regular vs irregular speech, sophisticated speech, etc. When speaking about the horizontal divisibility of language continuum offered by the ordinary members of language community and researchers, the most outstanding difference was that the ordinary members of language community had supplemented the binary dialect classification by two members. The taxonomy of the ordinary members of language community includes the Dzūkai and the Suvalkiečiai dialects alongside with the Highland and the Lowland dialects. When speaking about the vertical divisibility of language, it should be noted that no more such differences between the perspectives of the ordinary members of language community and sociolinguists have been observed; only the isoglosses of perception are much thicker. It should be noted that although the sample of the research is not large, the participation of the ordinary members of language community in the discussion has been definitely beneficial as it brought in the data contributing to the increasing awareness of the boundary problem both in geolinguistics and sociolinguistics.